Culture and Redemption : Religion, the Secular, and American Literature - Fessenden, Tracy (Book collections on Project MUSE., 2007)
Many Americans wish to believe that the United States, founded in religious tolerance, has gradually and naturally established a secular public sphere that is equally tolerant of all religions--or none. Culture and Redemption suggests otherwise. Tracy Fessenden contends that the uneven separation of church and state in America, far from safeguarding an arena for democratic flourishing, has functioned instead to promote particular forms of religious possibility while containing, suppressing, or excluding others. At a moment when questions about the appropriate role of religion in public life ha.